Superior Mesenteric Artery Syndrome at Pediatric Intensive Care Unit - Emine Burçe Yaşar; Mehmet Arda Kılınç; Bülent Karapınar (Galenos Yayinevi, 2017)
Superior mesenteric artery syndrome is a rare condition in patients who have oral feeding intolerance. Due to decreased fat tissue around the duodenum, the angle between the superior mesenteric artery and duodenum also decrease. Despite normal peristaltic bowel activity, nutrients cannot pass the duodenum. There are various causes for this. The basic treatment modality is early nutritional support. We share this article to increase awareness of this condition and recommend early nutritional support for immobilised patients.